Collodi educatore dell’Italia unita: tra scuola e cittadinanza - Franco Cambi (Studi sulla Formazione)
The essay focuses on the last part of Collodi's life and pedagogical work: this part was aimed at promoting the school system of unified Italy, indicating its task of shaping a new citizenship and spreading it through schools. According to Collodi, however, this action must always be accompanied by a critical and ironic attitude, which leaves room for a spirit of adventure in the education of young people. He therefore argues for the need to educate citizens with a strong ethical conscience but who are at the same time free and critical, through a democratic and liberal ethos, which Collodi had already defined as early as 1848.